A multibiomarker approach in Mytilus galloprovincialis to assess environmental quality - Cravo, Alexandra (2020)
A multibiomarker approach was carried out for the first time in the South Portuguese Coast using Mytilus galloprovincialis, to assess environmental quality, establish if there are adverse biological responses associated to different sources of anthropogenic contamination and to determine spatial and seasonal trends. For this purpose the battery of biomarkers selected was: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidases (GPx total and Se dependent), Cytochrome P450 component system, Glutathione-S-transferase (GST) and acetylcholinesterase (AChE), metallothionein (MT) and lead-delta-aminolevulinic acid dehydratase (ALAD), lipid peroxidation (LPO) and Condition Index (CI) along with the determination of PAHs and metals (Cd, Cu, Ni, Pb and Zn). Results show that despite the levels of both organic and metallic contaminants in these eight spots in the South Coast of Portugal not being particularly high compared with other contaminated/polluted sites worldwide, the selected battery of biomarkers responded efficiently to the environmental changes and allowed an environmental assessment between seasons and sites. Different spatial and seasonal responses were evident along the South Coast of Portugal, meaning that the contamination is not homogeneous. This does not only reflect different competition, origin and intensity of contamination, but also different environmental conditions (e.g. temperature, salinity). Along the South Portuguese Coast site 8 was the most contaminated, while site 2 was considered the least contaminated. Despite environmental factors possibly causing difficulties in the general interpretation of biomarker data, those that better responded to environmental contamination were CYP450, SOD-mit and T-GPx for the summation SigmaPAHs, MT (digestive gland) for metals (especially Cu), ALAD for Pb and LPO for both organic and metallic contamination. These biomarkers were also positively correlated with temperature in summer, revealing this as a more stressful/critical season. In future environmental contamination assessments there is no need to analyse the components b5, P418, NADH and NADPH of phase I MFO system, and MT in the gills, since their responses are not evident.